APLIKASI TEORI HIERARKI KEBUTUHAN MASLOW DALAM MENINGKATKAN MOTIVASI BELAJAR MAHASISWA - Sri Mendari, Anastasia (Widya Warta, 2010)
One of the motivation theories getting more positive appreciation in organizational management is Needs Hierarchy Theory of Abraham Maslow. He said that everyone has individual organized hierarchial needs from the bottom level to the top level. If the Needs Hierarchy Theory is applied in education, it may be expected to build the effectiveness of learning processes. Universities and/or higher learning colleges will be able to fulfill students’ needs in line with Maslow’s theory to improve their learning motivation. The crucial things of Maslow’s Hierarchy Needs Theory to increase students’ motivation lie between basic needs and growth needs. Universities and/or higher learning colleges should accomplish students’ basic needs in order to avoid learning disturbances or provide the balance of students’ learning needs.